Have we reached peak driving?: A 25-year decomposition of vehicle trends in Canada - Shenstone - Harris, Sarah (Université d'Ottawa | University of Ottawa, 2016)
The external costs of vehicle use are extensive, including traffic accidents, urban congestion, air pollution, and greenhouse gas emissions. Around the turn of the millennia, after decades of steady growth, per capita vehicle use in many western countries plateaued, or even declined. As there has been very little research conducted on Canadian driving patterns, this study aims to determine whether vehicle use has been changing in Canada, and how it compares to the United States. This research seeks to explain the influential factors behind vehicle use, specifically the effect of an aging population, rising income and gas prices, urbanization, and other elements. An index decomposition analysis was applied to weigh the relative influence of population growth, demographic changes, and individual car use, in both Canada and the United States, which was followed by a fixed-effect regression analysis to determine the influence of gas prices, income, and urbanization. Our results found that Canada has not experienced the same remarkable change in vehicle use compared to other western countries, but only a modest peak or plateau, with young adults leading the trend. Gas prices appear to be responsible for some of the change, although this was offset by the positive influence of population growth, and rising incomes. Although the quality of data needs to be improved, understanding driving trends in Canada can help policy makers manage vehicle use and its numerous associated externalities.